Vocalizações de Physalaemus cuvieri (ANURA, LEIUPERIDAE) ao longo do gradiente espacial no sul do Brasil. - Gambale, Priscilla Guedes (2013)
Studies on sexual evolution, associated with behavioral issues are bound to work in anuran bioacoustics because they are animals that use vocalizations for reproduction and social interactions in choruses. In anurans, advances in bioacoustics try to associate social contexts in which vocalizations are emitted, influences of environment in which they live, other individuals in choruses and morphological characters on vocalizations, as well as evaluate the transmission of the signal emitted over long distances. Although these works started a long time ago, there is little information for the group, mainly in the Neotropical region, an area of high diversity of amphibians. The first approach of this study assessed the social context in which vocalizations of Physalaemus cuvieri were emitted, as well as influences of abiotic, morphological characters and distance between males on acoustic parameters. We observed that advertisement calls were emitted to territorial delimitation and attract females in all males, while courtship calls were emitted in a few individuals when females were distant less than 20 cm of males. Acoustic parameters were influenced by environmental, morphological and social characteristics, generating useful information for system evolution of sexual selection and aggressive interactions. We test too influence of environmental characteristics on acoustic parameters over long distances. Results show evidence that degradation and attenuation occur in advertisement call of Physalaemus cuvieri and they are influenced by environmental, not morphological characteristics. More robust characterizations of microhabitats is necessary to obtain results more evident, due to small size of frogs. Other parameters can also be associated with the evolution of signals over long distances as physiological and phylogenetic characteristics, parasites, predators and social context. In short, results not only contributed to greater knowledge about the biology of the species, but also to generate data still little known and generate insights for future comparative studies and the evolution of communication systems in anurans.